Top-Down Dual-Interface Carrier Management for Highly Efficient and Stable Perovskite/Silicon Tandem Solar Cells - Xin Li; Zhiqin Ying; Shuo Li; Lei Chen; Meili Zhang; Linhui Liu; Xuchao Guo; Jun Wu; Yihan Sun; Chuanxiao Xiao; Yuheng Zeng; Jian Wu; et al. (Nano-Micro Letters)
Highlights An innovated top-down dual-interface carrier management strategy is developed to effectively improve both interfaces of the wide-bandgap perovskite using a multi-functionalized piperazinium chloride post-treatment. The 1.68 eV unencapsulated single-junction perovskite solar cells exhibit a champion PCE of 22.3%, with a record V OC × FF product (84.4% relative to the Shockley–Queisser limit). An impressive PCE of 31.5% for the 1.04 cm2 monolithic perovskite/silicon tandem solar cell based on silicon heterojunction bottom cell is demonstrated.